2019
DOI: 10.1080/14756366.2019.1574780
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and evaluation of anticancer, antiphospholipases, antiproteases, and antimetabolic syndrome activities of some 3H-quinazolin-4-one derivatives

Abstract: Some new 3 H -quinazolin-4-one derivatives were synthesised and screened for anticancer, antiphospholipases, antiproteases, and antimetabolic syndrome activities. Compound 15d was more potent in reducing the cell viabilities of HT-29 and SW620 cells lines to 38%, 36.7%, compared to 5-FU which demonstrated cell viabilities of 65.9 and 42.7% respectively. The IC 50 values of 15d were ∼20 µg/ml. Assessment of apoptotic act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 41 publications
1
17
0
Order By: Relevance
“…For the best compound ( Figure 7), an IC 50 of 3.0 μg/mL was calculated, which is a higher value than that observed for allopurinol (0.6 μg/mL). Cytotoxicity studies on colorectal cancer HT-29 and SW620 cell lines showed cellular viability nearly 40% at the concentration of 30 μg/mL [28].…”
Section: 14mentioning
confidence: 98%
“…For the best compound ( Figure 7), an IC 50 of 3.0 μg/mL was calculated, which is a higher value than that observed for allopurinol (0.6 μg/mL). Cytotoxicity studies on colorectal cancer HT-29 and SW620 cell lines showed cellular viability nearly 40% at the concentration of 30 μg/mL [28].…”
Section: 14mentioning
confidence: 98%
“…It was observed that the cytotoxicity of QDs apparently depends on the presence of a substituent located at carbon C-2 that could improve the activity of these compounds possibly due to the electronic effects. The detailed SAR analysis allows the determination of the chemical groups responsible for the desired therapeutic effects [ 42 , 44 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Over recent decade, various heterocyclic-based compounds possessing α-glucosidase inhibitory activities have been found [13][14][15][16][17][18][19][20][21][22][23][24] . For example, several pyrimidine derivatives have shown excellent inhibition potency [25][26][27][28] .…”
Section: Introductionmentioning
confidence: 99%